Persepsi Mahasiswa Ilmu Komunikasi Mengenai Isu Kesehatan Mental - Dewa, Faris Saputra (AL-MIKRAJ Jurnal Studi Islam dan Humaniora (E-ISSN 2745-4584), 2025)
The issue of mental health has been increasingly discussed in recent years, the increase in suicide and murder cases among students is strongly suspected to be due to mental health disorders in the perpetrators. Students are a group that is vulnerable to mental health disorders due to various factors. Research on mental health issues was conducted on 24 students of the communication science study program using an in-depth interview method. The results of the study showed that most students are aware of the importance of maintaining mental health, and they believe that the closest environment such as family and friends, as well as the use of social media have an influence on a person's mental health condition. Implementing a healthy lifestyle and an attitude of self-love are also believed to be the best way to avoid mental health disorders.